2019
DOI: 10.1152/ajpgi.00333.2018
|View full text |Cite
|
Sign up to set email alerts
|

Xenin-25 induces anion secretion by activating noncholinergic secretomotor neurons in the rat ileum

Abstract: Xenin-25 is a neurotensin-like peptide that is secreted by enteroendocrine cells in the small intestine. Xenin-8 is reported to augment duodenal anion secretion by activating afferent neural pathways. The intrinsic neuronal circuits mediating the xenin-25-induced anion secretion were characterized using the Ussing-chambered, mucosa-submucosa preparation from the rat ileum. Serosal application of xenin-25 increased the short-circuit current in a concentration-dependent manner. The responses were abolished by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…VIP is mainly localized in the myenteric and submucosal neurons and nerve terminals in the GI tract 20, 21 . Endogenous VIP is released by numerous stimuli such as acetylcholine (ACh) 22 , ATP 23 , serotonin (5-HT) 24 , substance P (SP) 25 , GLP-2 26 , and xenin-25 27 from at least two populations of VIP-positive nerves: cholinergic and non-cholinergic VIP-releasing nerves. In guinea pig small intestine, most VIP-positive nerves in the mucosa and submucosa are non-cholinergic secretomotor neurons 28 and well colocalized with neuronal nitric oxide synthase (nNOS) in human colonic circular muscles 29 .…”
Section: Vip and Its Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…VIP is mainly localized in the myenteric and submucosal neurons and nerve terminals in the GI tract 20, 21 . Endogenous VIP is released by numerous stimuli such as acetylcholine (ACh) 22 , ATP 23 , serotonin (5-HT) 24 , substance P (SP) 25 , GLP-2 26 , and xenin-25 27 from at least two populations of VIP-positive nerves: cholinergic and non-cholinergic VIP-releasing nerves. In guinea pig small intestine, most VIP-positive nerves in the mucosa and submucosa are non-cholinergic secretomotor neurons 28 and well colocalized with neuronal nitric oxide synthase (nNOS) in human colonic circular muscles 29 .…”
Section: Vip and Its Receptorsmentioning
confidence: 99%
“…VPAC1 in mice and humans is predominantly expressed in the colon relative to the small intestine 44 and is predominantly expressed in the mucosa and submucosa compared to the muscle layers in rat ileum 27 , suggesting that VIP effects on epithelial functions, including ion transport, mucus secretion, tight junction protein expression, and cell proliferation, are mainly mediated via VPAC1 activation. VPAC1 localization in the epithelial cells is thought to be on the basolateral membranes, since serosally applied VIP increases electrogenic anion secretion in the small and large intestine 45, 46 .…”
Section: Vip and Its Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xenin acts on the neurotensin receptor (Fuerle, 1998). Furthermore, increases in Cl − and HCO 3 − secretion induced by Xenin25 are mediated by the NT receptors in the enteric nervous system (Kaji et al, 2017; Kuwahara et al, 2019). Xenin25 plasma concentrations increase in peripheral circulation after food intake (Fuerle et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the GI tract, Xenin25 affects various physiological functions by modulating GI motility, inhibiting gastric acid secretion, and stimulating exocrine pancreatic secretion (Chowdhury et al, 2013; Fuerle, 1998; Fuerle et al, 1997). We recently reported that Xenin25 affects intestinal ion transport through the activation of ENS; Xenin25 induces anion secretion through the activation of IPANs and noncholinergic secretomotor neurons in rat duodenum and ileum, respectively (Kaji et al, 2017; Kuwahara et al, 2019). Based on an in vitro experiment, Xenin25 has excitatory and inhibitory effects on smooth muscle activity in the guinea pig GI tract; Xenin induces a biphasic motor response of the small intestine with involvement of the neurotensin receptor, cooperating with muscarinic, purinergic, and tachykinin‐related mechanisms (Fuerle et al, 1996, 2002).…”
Section: Introductionmentioning
confidence: 99%